Pemenuhan Hak-hak Narapidana Berdasarkan Asas Persamaan di Hadapan Hukum (Studi Kasus Lembaga Pemasyarakatan Klas II A Yogyakarta) - Elviannisa & Faisal Luqman Hakim (UIN Sunan Kalijaga Yogyakarta, 2016)
This study concluded that the Prison Class II A Yogyakarta has tried to apply the principle of equality before the law despite the obstacles and the fulfillment of the rights of prisoners, prison following the procedure for the fulfillment of the rights of prisoners in accordance with Government Regulation No. 32 of 1999 on the Terms and Procedures Patronage citizen rights Implementation Corrections for example still a right prisoners to obtain assimilation has not been fulfilled. Based on the results of interviews with prisoners by officers such as the difference in the closeness made officers.